Does Governance Disclosure in Integrated Reporting Create Value? Evidence from Indonesia - Ayu Febrianti Dolok Saribu; Ika Permatasari Permatasari (Majapahit Journal of Islamic Finance and Management, 2026)
Corporate reporting has undergone a paradigm shift, where investors increasingly demand non-financial information, particularly governance disclosure, to support informed decision-making. However, studies on the value relevance of governance disclosure in Integrated Reporting (IR) have shown inconsistent results, especially in the context of developing countries. This study is grounded in voluntary disclosure theory, which suggests that governance disclosure within IR can reduce information asymmetry and signal management quality, thereby influencing investor market perceptions. This study used panel data consisting of 60 observations over the period 2021–2024, derived from companies listed in the ESG indices on the Indonesia Stock Exchange. Governance disclosure is measured using the Governance Disclosure Index (GDI), constructed through content analysis of integrated reports based on the IIRC framework and the Ohlson (1995) as our value relevance model. The regression result indicated that GDI has a positive effect on firm market value, supporting that governance disclosure in IR has value for investors. Our finding suggests that comprehensive governance disclosure enhances investor confidence and firm value within the context of voluntary IR adoption in Indonesia.